تحسين إدارة الصيانة للمباني الحكومية - جراد, فايز; الحسن, باسل (Latakia University Journal -Engineering Sciences Series, 2016)
لقد حاز موضوع الصيانة على اهتمام عالمي متزايد في مختلف مجالات البحث العلمي، ونتيجة لذلك حدث تغير نوعي في صيانة الأبنية من المنهج الوقائي والاصلاحي إلى المنهج التوقعي، ويتم ذلك من خلال موديل تقييمي ليدعم ويساعد إدارة المنشأة في اختيار البدائل واتخاذ القرارات المناسبة في الصيانة بما يتلاءم ووضع البناء وموازنة الصيانة.وقد لوحظ أن هناك نقص في فعالية الصيانة للأبنية الحكومية في سوريا، حيث أن المنهج المتبع هو القيام بالصيانة عند حدوث العطل مما يؤدي إلى تراكم في الأعطال.تم في هذا البحث دراسة أسباب الصيانة للمباني الحكومية ودرجة أهمية كل عنصر من عناصر الصيانة وذلك من خلال تصميم استبيان قُسم فيه البناء إلى مكونات أساسية وعناصر ثم ربط كل عنصر ببنود الصيانة التي تنفذ فيه، وفي نهاية البحث تم وضع نماذج رياضية هي موديلات انتكاس تساعد بالتنبؤ بأعمال الصيانة وتوزيع الموازنة، وللتأكد من صحة هذه الموديلات تم تطبيقها على دراسة حالة السكن الجامعي في جامعة تشرين.Building maintenance is gaining an increasing worldwide recognition in many fields of study.as a result; a remarkable shift in building maintenance management from preventive approach to predictive approach is taking a place now a days. That is achievable through building of an evaluative model to assess a variety of alternative decisions and make the right decisions, taking in the consideration building condition and the available budget for maintenance. In Syria, there is lack of effective building maintenance for governmental buildings because we use an approach depends on doing the work after the fault happened, that leads to deteriorating in the all building's parts.In this paper, we study maintenance reasons and importance degree for every single components by designing questionnaire, divide the building in to its essential parts and components, and link them to maintenance works.At the end, we get mathematical models called deterioration models assist in predictable maintenance works and distributing the budget, and to make sure about validity of these models we apply them in the dormitory in Tishreen University.